Ryzyko prowadzenia działalności gospodarczej przez zakłady opieki zdrowotnej (wybrane obszary ryzyka) - Orliński, Ryszard (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The concept of risk is usually connected with a possibility of not executing decisions or actions. In medical activity, like in others, a political, economic, organizational or medical risk may appear. Health care units which run business activity shall take account of risk especially while taking executive decisions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 282-291